Tajikistan : Poverty Assessment - World Bank (World Bank, 2012)
Despite Tajikistan's sustained economic growth of the past few years and the country's notable achievements, poverty and low standards of living remain a pressing problem for the majority of Tajik people. Poverty reduction is therefore one of the priority goals of the Government of the Republic of Tajikistan, of its national and international partners, and of Tajik society as a whole. This report presents a comprehensive analysis of poverty in Tajikistan using the most recent Tajikistan Living Standards Survey (TLSS) data, which is for 2007. The report provides an in-depth analysis of poverty dynamics (since 2003); a poverty profile; the linkages between labor markets, migration, and poverty; the importance of social transfers for poverty alleviation; and the key issues in the health and education sectors. The report also simulates possible poverty impacts from the reduction in migration and remittances related to the global financial crisis. The report shows that migration and remittances are a significant factor in the observed improvements in living standards between 2003 and 2007. However, the expected reduction in migration and remittances due to the financial crisis is likely to result in increased poverty levels, vulnerability, and higher income inequality, at least in the short term.